2009
DOI: 10.1089/adt.2008.179
|View full text |Cite
|
Sign up to set email alerts
|

Agonists of the Orphan Human G2A Receptor Identified from Inducible G2A Expression and β-Lactamase Reporter Screen

Abstract: The G protein-coupled receptor (GPCR) G2A (for G2 accumulation) was identified as a stress-inducible antiproliferative cell cycle regulator. Targeted G2A gene deletion in mice resulted in systemic lupus erythematosus-like and atherosclerotic lesion phenotypes. These findings suggested that G2A may be a therapeutic target for cancers and autoimmune and cardiovascular diseases. The G2A receptor is cytotoxic upon ectopic expression, and its cognate ligand has not been identified, making it difficult to generate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Indeed, Lp-PLA 2 appears to be well placed to modulate macrophage accumulation and function due to its ability to cleave oxidized phospholipids generating lysoPC, lysoPS and various oxidized FFAs including 9-and 13-HODE. 18,49 Although still somewhat controversial, 50 all three lipid products have been described as ligands for the G-protein-coupled receptor G2A, 51,52 which is highly expressed in peripheral blood leukocytes and has been proposed to not only attract phagocytes to apoptotic cells but to facilitate their removal. Interestingly, lyso-PS can be generated by two distinct pathways to influence phagocytosis; by cleavage of externalized PSox, as described herein by Lp-PLA 2 , or generated intracellularly via a NADPH oxidasedependent pathway by neutrophils.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Lp-PLA 2 appears to be well placed to modulate macrophage accumulation and function due to its ability to cleave oxidized phospholipids generating lysoPC, lysoPS and various oxidized FFAs including 9-and 13-HODE. 18,49 Although still somewhat controversial, 50 all three lipid products have been described as ligands for the G-protein-coupled receptor G2A, 51,52 which is highly expressed in peripheral blood leukocytes and has been proposed to not only attract phagocytes to apoptotic cells but to facilitate their removal. Interestingly, lyso-PS can be generated by two distinct pathways to influence phagocytosis; by cleavage of externalized PSox, as described herein by Lp-PLA 2 , or generated intracellularly via a NADPH oxidasedependent pathway by neutrophils.…”
Section: Resultsmentioning
confidence: 99%
“…PAFR is the only known receptor that responds to PAF, although the family of lipid receptors is large, and there are quite a few orphan receptors that remain unexplored and incompletely characterized (reviewed in (53)). The G2A receptor was initially characterized as responding to lysoPC, but this finding has recently been reconsidered (56). Likewise, several groups have reported that the actions of lysoPC are dependent on the presence of the receptor GPR4 (57, 58) yet the receptor itself has been characterized alternatively as ligand-independent (59) or proton sensing (60).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that Compound 3 only inhibited doxycycline-induced constitutive bla activity in GPR23-expressing cells and not in another cell line expressing the G2A receptor under the same T-REx™ regulation system indicating the effect is GPR23-specific. 30 These results suggest that Compound 3 binds the GPR23 receptor and modulates its constitutive activity at a domain other than the LPA-binding site.…”
Section: Discussionmentioning
confidence: 87%